Primary Corneal Squamous Cell Carcinoma in a Dog: Clinical and Histopathological Evaluation. (2nd February 2012) - Barsotti, Giovanni; Ressel, Lorenzo; Finotello, Riccardo; Marchetti, Veronica; Millanta, Francesca
Abstract : An 8-year-old male pug with a 12-month history of a progressive nonpainful mass on the left cornea was evaluated. Ocular examination showed a severe bilateral keratoconjunctivitis sicca, pigmentary keratitis, and an exophytic irregular pink mass occupying approximately 75% of the total corneal surface of the left eye. A squamous cell carcinoma (SCC) was suspected on cytology, and clinical investigations showed no evidence of metastases. A transpalpebral enucleation was therefore performed, and the diagnosis of SCC was confirmed on histopathology. Immunohistochemical investigations showed that the neoplastic cells were pan-cytokeratin positive and vimentin negative. Additionally, nuclei immunoreactive to Ki-67 antigen were detected. Tumor cells were also negative to p53. Immunoreactivity to COX-2 was found in less than 10% of the neoplastic cells. No adjuvant therapies were instituted, and no evidence of local recurrence or distance metastasis was identified during the 24-month follow-up period.